ISOLASI DAN IDENTIFIKASI BAKTERI PENGHASIL PROTEASE EKSTRASELULER DARI LIMBAH CAIR INDUSTRI TAHU - Wiwi Kusumasari; Ana Indrayati; Lukito Mindi Cahyo (Sekolah Tinggi Ilmu Kesehatan ISFI Banjarmasin, 2023)
Tofu waste that is discharged into the aquatic environment has a negative impact on the quality of the water around the tofu liquid waste disposal site. Industrial enzyme production is currently dominated by proteases. Proteases in the pharmaceutical field support the absorption of proteins in the digestive tract, as active cosmetic ingredients. This study aims to isolate, identify protease-producing bacteria from tofu wastewater, determine the total protein content and enzyme activity index of 5 isolates of protease-producing bacteria. Tofu wastewater bacteria were isolated with Skim Milk Agar medium. 5 bacterial isolates were selected which produced the widest clear zones, different colony characters, identified by morphological tests, gram staining tests, and biochemical tests. Five isolates were made into a bacterial suspension isolated from crude protease extract and the protease level was determined using the Bicinchoninic Acid method, and the protease activity was tested. Five bacterial colonies showed that colony 1 and colony 2 included Gram positive bacteria, colonies 3, 4 and 5 included Gram negative bacteria. The value of total protein content in the tofu industrial wastewater from the five colonies respectively: 219.93; 833,267; 421,267; 81,267; and 38.6 µg/µL. The highest proteolytic activity test was in sample 2 of 2.13.